Development of a Creative Gymnastics Model to Improve Basic Locomotor Movements in Elementary School Students - Ariska, Dewi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2018)
This research aims to produce a creative gymnastics learning model for basic locomotor movements for elementary school children. This research uses the Research & Development (R&D) research method from Borg and Gall in Sugiyono. Small group testing of 10 students at the Negeri 40/XI Talang Duku Elementary School, Muaro Jambi Regency, model items, in large group testing 18 students with 28 model items. Test the effectiveness of 10 students using a locomotor test with the one group pretest posttest design by obtaining effectiveness test scores with an average pre-test result of 34.30 and an average post-test result of 69.90 with sig. 0.00 then the data is declared homogeneous therefore the data read is equal variances assumed, then the t-count is greater than the t-table (20,463>2.26216) with a significance level of 1%, df 9 and sig. (2-tailed) = 0.000 < 0.05 with an explanation of the application of the creative gymnastics learning model for basic locomotor movements in elementary school children effectively. Based on the results obtained, it can be concluded that: (1) With this creative gymnastics learning model, students can learn more effectively and efficiently, (2) with this creative gymnastics learning model, improvements are obtained which are shown in the pre-test and post-test results. there are significant differences.